Eriodictyol-induced anti-cancer and apoptotic effects in human hepatocellular carcinoma cells are associated with cell cycle arrest and modulation of apoptosis-related proteins - Fang Wang; Yu-Hang Wang; Jing-Jing Wang; He-Lin Xu; Chang-Miao Wang (Bangladesh Pharmacological Society, 2016)
The objective of the present study was to investigate the anti-cancer effects of eriodictyol in human hepatocellular carcinoma cells (Hep-G2) and normal liver hepatocyte cell line (AML12) along with evaluating its mode of action. Sulforhodamine B assay was used to evaluate the cytotoxic effect of the compound while as fluorescence microscopy was involved to demonstrate the effect of eriodictyol on cellular apoptosis. Flow cytometry was used to investigate the effect of eriodictyol on cell cycle while Western blot analysis revealed the effect on apoptosis-related protein expressions. Results indicate that eriodictyol-induced selective and concentration-dependent cytotoxic effect on Hep-G2 cancer cells while AML12 normal liver cells were very less susceptible to its effect. Eriodictyol-induced apoptosis related morphological changes including chromatin condensation and nuclear fragmentation. It also induced G2/M cell cycle arrest in these cells. Eriodictyol led to up-regulation of Bax and PARP and down-regulation of Bcl-2 protein. Video Clip of Methodology: Flow cytometry assay: 35 sec   Full Screen  Alternate